The Associations Among Physical Activity, Quality of Life, and Self-Concept in Children and Adolescents With Disabilities: A Moderated Mediation Model - Yang, Wen; Yu, Jane Jie; Wong, Stephen Heung-Sang; Sum, Raymond Kim-Wai; Li, Ming Hui; Sit, Cindy Hui-Ping (Frontiers in Pediatrics, 2022)
Objectives: This study aimed to examine a moderated mediation model of the associations among physical activity (PA), quality of life (QoL), and self-concept (SC) in children and adolescents with physical disabilities (PDs) and intellectual disabilities (IDs). Methods: A total of 288 children and adolescents with PDs and IDs, aged between 6 and 17 years, were recruited from 16 special schools in Hong Kong. PA, QoL, and SC were measured using the Physical Activity Questionnaire for Older Children, Pediatric Quality of Life Inventory, and Physical Self-Description Questionnaire Short Form, respectively. Mediation (i.e., PA, QoL, and SC) and moderation analyses (i.e., age, sex, and parental education level) were conducted by structural equation modelling (SEM) using the M plus and PROCESS macro for SPSS. Results: PA was positively associated with SC (PDs: β = 0.373; IDs: β = 0.343), and SC significantly mediated the associations between PA and QoL in children and adolescents with PDs (parent proxy-report QoL: β = 0.114; self-report QoL: β = 0.141) and IDs (self-report QoL: β = 0.204). The mediating effects of SC accounted for 16% and 15% of the total effects of PA on QoL (parent proxy-report and self-report) respectively in participants with PDs, and 8% and 4% respectively in those with IDs. Males and participants with higher parental education levels reported stronger associations among PA, QoL, and SC than their counterparts. Conclusions: This study supports mediating and moderating effects on the associations among PA, QoL, and SC in children and adolescents with PDs and IDs. Future researchers should consider PA intervention in mental health services and provide tailor-made PA programmes based on personal and environmental factors for children and adolescents with disabilities.